Across Oceans and Revolutions: Law and Slavery in French Saint‐Domingue and Beyond. Issue 3 (10th July 2014) - Wood, Laurie M.
<x xml:space="preserve">Abstract</x> New work on colonial legal regimes suggests new pathways for scholarship on legal regimes, legal consciousness, judicial personnel, and the Atlantic world. Malick Ghachem's recent book, The Old Regime and the Haitian Revolution (2012), introduces scholars to one legal regime—that of the French plantation colony of Saint‐Domingue—to show how enslaved and free people continually negotiated the terms of master sovereignty and manumission. This debate lasted from Saint‐Domingue's establishment as a slave society in the seventeenth century to its revolution in the 1790s, which overthrew the slave regime and culminated in independence in 1804 as the republic of Haiti.